Consecutive Kummell's Disease Combined with Parkinson's Disease and Experienced Internal Fixation Failure: A Case Report and Literature Review. Issue 7 (27th May 2022) - Zhan, Yi; He, Guiping; Yang, Huiming; Gao, Wenjie; Yuan, Wei; Sun, Honghui; Hao, Dingjun; Wang, Biao
Abstract : Background: The continuous occurrence of Kummell's disease is extremely rare in clinical practice, and its treatment is difficult. The study aimed to present a rare case of consecutive Kummell's disease combined with Parkinson's disease (PD) and experienced internal fixation failure. Case presentation: A 69‐year‐old female patient had a history of PD for 10 years, and was treated by posterior decompression, fixation, and fusion because of Kummell's disease of T12 with neurological damage. The patient's back pain and lower limb pain were significantly improved after surgery. Twenty‐two months later, the patient was rehospitalized for Kummell's disease of L4 with neuropathic pain of left lower extremity. She received almost identical surgical procedures as T12 lesion, and the difference was no L4 vertebroplasty preformed due to the fact that the L4 vertebrae collapse was not obvious, the intravertebral vacuum cleft (IVC) range was small, and the pedicle screw fixation strength was high. The pain symptoms were significantly relieved after operation. Unfortunately, there was a complication of internal fixation failure that occurred a month later, and a revision operation was carried out. Conclusion: Osteoporosis combined with PD may lead patients to become prone to consecutive Kummell's disease, and patients are prone to experience failure of internal fixation. Bone cement filling of vertebral IVC and effective support of anterior vertebral column are very important procedures to ensure the clinical efficacy of treating Kummell's disease. Abstract : We present the case of a 69‐year‐old female patient with consecutive Kummell's disease combined with Parkinson's disease who was treated with pedicle screw fixation. Unfortunately, there was a complication of internal fixation failure that occurred a month later, and a revision operation was carried out.